Assessment of Forest Conservation Practices among Women Shea Nut Collectors in Baruten Local Government Area, Kwara State, Nigeria - Sikiru Ibrahim-Olesin; Lateef Lawal Adefalu; Sidiqat Adeyemi Aderinoye-Abdulwahab; Hubedat Kora Abdullahi; Dener Márcio da Silva Oliveira; Diego Antonio França de Freitas (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Concerns over unsustainable harvesting of shea butter trees and consequent forest degradation in Kwara State, Nigeria, highlight the need to focus on women shea collectors as key actors in conservation and restoration. This study assessed forest conservation practices (FCPs) among women shea collectors in Baruten Local Government Area, examining their socioeconomic profiles, information sources, knowledge, usage, and constraints. A probability‑based, two‑stage stratified cluster sampling with proportional allocation selected 150 women shea collectors. Data were collected via structured interview schedules and analyzed using descriptive statistics and multiple regression to identify socioeconomic determinants of FCPs usage. Findings show the most frequently used practices were establishment of protected areas (mean = 4.38), forest fire management (mean = 3.15), and controlled burning (mean = 3.14); the least utilized were sustainable logging practices (mean = 2.17), forest restoration projects (mean = 1.87), and agroforestry (mean = 1.58). Major constraints included fire outbreaks (mean = 3.19), indiscriminate logging (mean = 3.11), and grazing by Fulani herders (mean = 2.34). Multiple regression revealed significant associations between FCP usage and age (p = 0.000), education (p = 0.000), average monthly income (p = 0.007), and household size (p = 0.000). Older and married collectors showed greater adoption of FCPs. The study concludes that women shea collectors are active participants in conservation but face ecological and socio-institutional barriers. It recommends that strengthening awareness and training on underutilized practices like agroforestry and sustainable logging, delivered through trusted community-based channels, could enhance conservation outcomes and resilience among shea nut collectors.